2014
DOI: 10.1002/eji.201444859
|View full text |Cite
|
Sign up to set email alerts
|

Signal regulatory protein alpha (SIRPα) regulates the homeostasis of CD103+CD11b+DCs in the intestinal lamina propria

Abstract: Signal regulatory protein alpha (SIRPα/CD172a) is a conserved transmembrane protein thought to play an inhibitory role in immune function by binding the ubiquitous ligand CD47. SIRPα expression has been used to identify dendritic cell subsets across species and here we examined its expression and function on intestinal DCs in mice. Normal mucosa contains four subsets of DCs based on their expression of CD103 and CD11b and three of these express SIRPα. However, loss of SIRPα signaling in mice leads to a selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…CD4 and CD8 α were also differently expressed among the subsets whereas co‐stimulatory molecules, CD80 and CD86, were equally expressed. Recent studies have revealed that DCs can be classified into subsets based on XCR1 and CD172a expression . Consistent with the previous studies, CD11b − CD103 + DCs including PD‐L1 High and PD‐L1 Low subsets expressed XCR1 but not CD172a whereas CD11b + CD103 + and CD11b + CD103 − DCs expressed CD172a but not XCR1.…”
Section: Resultssupporting
confidence: 86%
“…CD4 and CD8 α were also differently expressed among the subsets whereas co‐stimulatory molecules, CD80 and CD86, were equally expressed. Recent studies have revealed that DCs can be classified into subsets based on XCR1 and CD172a expression . Consistent with the previous studies, CD11b − CD103 + DCs including PD‐L1 High and PD‐L1 Low subsets expressed XCR1 but not CD172a whereas CD11b + CD103 + and CD11b + CD103 − DCs expressed CD172a but not XCR1.…”
Section: Resultssupporting
confidence: 86%
“…The same group subsequently showed that treatment with CD47-Fc conferred protection via a Th17-dependent mechanism [ 67 ]. Consistent with these data, a recent study by a different group found decreased numbers of Th17 cells in healthy intestinal mucosa of cd47 -null and SIRPα signaling-deficient mice, and a corresponding defective Th17 response to Citrobacter infection [ 68 ]. In this context, our data indicates that a defective Th17 response may contribute to the decreased resistance of cd47 -null mice to C .…”
Section: Discussionsupporting
confidence: 71%
“… 9 , 10 CX3CR1 was virtually absent in all colonic DC (see Figure 2 E ) but was expressed by macrophages, 17 whereas the GI-tract homing β7 integrin was expressed by the majority of colonic DC, with all CD103 + DC being positive. SIRPα, which regulates homeostatic properties of intestinal DC, 44 was typically coexpressed with the inhibitory receptor Ig-like transcript 3 (ILT3), 45 with no differences between CD103 - SIRPα + and CD103 + SIRPα + DC; CD103 + SIRPα − DC were ILT3 − . Conversely, ILT3 − DC displayed a higher expression of the costimulatory molecule CD40 (see Figure 2 E ).…”
Section: Resultsmentioning
confidence: 99%